The study of ensemble properties of complex signals obtained by time interval permutation - Indyk, Serhii; Lysechko, Volodymyr (Національний технічний університет "Харківський політехнічний інститут", 2020)
The results of statistical analysis of cross-correlation properties of complex signals’ ensembles, were obtained due to time interval permutations are presented in this paper. The essence of the method is to apply the division of short videopulse sequencesat the level of intervals with low interaction in the time domain with different numbers of pulses. By applying the cross-correlation analysis, the maximum emission values of the side lobes of the cross-correlation functions are calculated and itstotal averagevalue is determined. Based on the obtained values, a series is formed in which the first position is occupied by a time interval in which the value of the maximum emissions of the side lobes of the cross-correlation function has an average value. The determination of the following time intervals is based on the analysis of the rating series and the arrangement of values is carried out in accordance with the selected total average value. Thus, a new average range of the maximum emission values of the side lobes of the cross-correlation function is formed. The average range increases the number of ensembles with satisfactory cross-correlation properties for use in radio communication systems with code division multiplexing, and minimal interaction between signals in the time domain reduces multiple access interference.

У статті наведено результати статистичного аналізу взаємокореляційних властивостей ансамблів складних сигналів, які були отримані за рахунок перестановок часових інтервалів. Суть методу полягає у застосуванні розбиття послідовностей коротких відеоімпульсів на рівні інтервали з низькою взаємодією у часовій області з різною кількістю імпульсів. Шляхом застосування взаємокореляційного аналізу здійснюють розрахунок значень максимальних викидів бічних пелюсток функцій взаємної кореляції та визначають їх загальне середнє значення. На основі отриманих значень складають ряд, в якому першу позицію займає часовий інтервал, у якому величина максимальних викидів бокових пелюсток функції взаємної кореляції має середнє значення. Визначення наступних часових інтервалів відбувається на основі аналізу рейтингового ряду і розстановка значень проводиться у відповідності до обраного загального середнього значення. Таким чином формують новий усереднений ряд значень максимальних викидів бокових пелюсток функції взаємної кореляції, завдяки якому збільшується кількість ансамблів із задовільними взаємокореляційними властивостями для використання всистемах радіозв’язку з кодовим розділенням каналів, а мінімальна взаємодія між сигналами у часовій області призводить до зменшення завад множинного доступу.
Дослідження властивостей ансамблів складних сигналів, отриманих шляхом перестановок часових інтервалів
Keywords: multiple access interference; videopulse; signal base; signal spectrum width; завада множинного доступу; відео імпульс; база сигналу; ширина спектру сигналу